2021
DOI: 10.3390/nu13082567
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet, Physical Activity, and Hypertension—A Narrative Review

Abstract: Several studies link cardiovascular diseases (CVD) with unhealthy lifestyles (unhealthy dietary habits, alcohol consumption, smoking, and low levels of physical activity). Therefore, the strong need for CVD prevention may be pursued through an improved control of CVD risk factors (impaired lipid and glycemic profiles, high blood pressure, and obesity), which is achievable through an overall intervention aimed to favor a healthy lifestyle. Focusing on diet, different recommendations emphasize the need to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…New advances in the prevention, diagnosis, and treatment of main cardiovascular disease as well as CV risk factors are required in order to improve the ability to (1) identify patients at higher risk early on; (2) identify early markers of subclinical cardiovascular disease; (3) improve treatment algorithms for the different clinical syndromes; (4) assess residual risk and follow-up optimization; (5) prevent recurrences. This is the challenge of the forthcoming decades, and the clinicians of the future must be ready to meet it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New advances in the prevention, diagnosis, and treatment of main cardiovascular disease as well as CV risk factors are required in order to improve the ability to (1) identify patients at higher risk early on; (2) identify early markers of subclinical cardiovascular disease; (3) improve treatment algorithms for the different clinical syndromes; (4) assess residual risk and follow-up optimization; (5) prevent recurrences. This is the challenge of the forthcoming decades, and the clinicians of the future must be ready to meet it.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive intervention that promotes a healthy lifestyle in an individual (abolition of cigarette smoking, regular physical activity, body weight control, adoption of a Mediterranean diet, etc.) would allow a cross-sectional health benefit that would go well beyond CVD improvement and control [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. A healthy diet, especially the Mediterranean diet, has been demonstrated to significantly influence CV risk, actively contributing to the control of major risk factors such as hypercholesterolemia, high BP, diabetes and obesity [ 5 , 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for hypertension include genetic factors, age and a variety of adverse lifestyle [ 8 ]. Worldwide studies have demonstrated that the genetic tendency of hypertension is very obvious, with 30% ~ 50% of an individual's risk of hypertension attributable to genetic factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…KD is a high-fat (providing a range of 55 to 90% calories as fat), adequate protein (accounts for 30-35% of the daily caloric requirement supplied; minimum of 1 g/kg of protein), lowcarbohydrate diet (only 5-10% of total calorie intakes are provided by carbohydrates, less than 50 g/day) 5 . The term KD currently refers to any dietary therapy which results in a metabolic ketogenic state.…”
Section: Introductionmentioning
confidence: 99%